Applications of Polycyclic Aromatic Hydrocarbons to Assess the Source and Thermal Maturity of the Crude Oils from the Lower Indus Basin, Pakistan - Asif, M.; Nazir, A.; Fazeelat, T.; Grice, Kliti; Nasir, S.; Saleem, A. (Taylor & Francis Group, 2011)
A suite of six crude oils from Lower Indus Basin, Pakistan, were analysed for geochemical characterization of source organic matter (OM) and thermal maturity. Distribution of polycyclic aromatic hydrocarbons (PAHs), alkylnaphthalenes, alkylphenanthrenes, alkyldibenzothiophenes, and aromatic biomarkers were reported from aromatic fractions of the crude oils. The aromatic hydrocarbons parameters revealed a higher thermal maturity of OM of source rock-generated Lower Indus Basin oils. Calculated vitrinite reflectance values from the methylphenanthrenes index 1 (MPI-1) and methyldibenzothiophene ratio (MDR) indicate that most of the oils reached a late oil generation window of thermal maturity. PAH distributions revealed the oils of two different origins are present in the Lower Indus Basin; two oil samples indicate aquatic source of OM and the aromatic biomarker distributions of retene, 1-MP, and 1,7-DMP indicate a significant contribution of land plant OM in the other four oils. This is the first study to report the distribution of aromatic hydrocarbons from Lower Indus Basin crude oils.